Fanaticism of K-Popers on Community Accounts and BTS- Fans on Instagram - Hanisa Hanisa; A.Dian Fitriana; Nurhakki Nurhakki (Universitas Lambung Mangkurat, 2024)
This article aims to determine the symbolic reality and subjective reality of fanatic behavior of K-Popers in editing content on community and fan accounts on Instagram. This research uses qualitative research methods and a descriptive phenomenological approach. The data collection technique is observation and interviews with K-Pop account admins on Instagram. The informants for this research are admin @yoyuby93, @agustdmine93, @yoza_anjelisa, and @asrianisj. The data was analyzed systematically through the stages of data reduction, data presentation and drawing conclusions. The results of this research show that (1) The fanatic behavior of K-Popers in editing content on the Instagram accounts of community account admins and BTS fans does not meet objective reality. Because some of the content created by the admin is the result of edits and illustrations according to his imagination, some are even not bound by the rules for creating content so the resulting content is uncontrolled and doesn't make sense. (2) The symbolic reality of the fanaticism of community account admins and BTS fans in editing content where admins always use certain symbols or elements to express their love, enjoyment, loyalty and pride towards K-Pop idols. (3) The subjective reality of the fanatic behavior of community account admins and BTS fans in editing content where the admin's feelings as a K-Pop fan influence the way he edits content because idols act as admin content ideas where they are inspired by the expressions, style and charm of their K-Pop idols.